DINAMIKA KARBON (C) AKIBAT ALIH GUNA LAHAN HUTAN MENJADI LAHAN PERTANIAN - A. Monde; N. Sinukaban; K. Murtilaksono; N. Pandjaitan (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
Land use changes from forest to agricultural farms have been incessantly occurring in Indonesia. This condition will have harmful effects on nature equilibrium if uncontrolled. Forest can effectively absorbed carbon, in contrast deforestation will result in the release of carbon dioxide (CO2) to the atmosphere. The research results indicated that significant carbon losses have taken place due to forest changes to agricultural farms.  Agro-forestry system can lessen these losses from vegetation, litter, soil and due to soil erosion. Agricultural farm with maize and peanut produced lower carbon than forest and vanilla agro-forestry.